A Case Study Highlighting the Impact of Dadhimadi Ghrut on Pandu Roga w.s.r. to Iron Deficiency Anemia - Aishwarya Pandey,; Ashok Kumar Sharma, (International Journal of Ayurveda and Pharma Research, 2024)
Context: In India, the most common cause of anemia is a nutritional iron deficiency. The nearby term for iron deficiency anemia (IDA) in Ayurveda is Pandu Roga. Due to the high prevalence of IDA in society and the frequent side effects of oral allopathic iron preparations, Ayurvedic ghee was given in a case report of a woman suffering from IDA in order to evaluate the efficacy of Dadhimadhi Ghrut, an Ayurvedic remedy. Aim: Evaluation of role of Dadhimadhi Ghrut in haemoglobin level and iron binding capacity in a patient suffering from Pandu (IDA). Design: Case report - Clinical study. Materials and Methods: The study was conducted on a woman of IDA for a period of 12 weeks. Clinical features and hematological parameters were documented before, during and after treatment. Results: The present study shows that the trial drug Dadhimadhi Ghrut is effective to improve clinical features and hematological parameters significantly. The medicine is effective to increase the hemoglobin level g/dL (8.4 -10.1g/dL) in 6 weeks and 3.61g/dL (8.4 -12.01g/dL) in 15 weeks. No adverse effect of the trial drug was observed during the study. Conclusion: The results suggest that Dadhimadhi Ghrut is significantly effective in the management of IDA in anemic woman.